EKSISTENSI PLTMH CINTA MEKAR DALAM PEMBERDAYAAN MASYARAKAT MELALUI KOPERASI MEKAR SARI DI DESA CINTA MEKAR KECAMATAN SERANG PANJANG KABUPATEN SUBANG PROVINSI JAWA BARAT - Ariyanto, Eko; Setiono, Iman; Sasmoko, Priyo; Pamungkas, Zaka Adi (Gema Teknologi, 2018)
PLTMH located in CintaMekar Village, SerangPanjang Sub-District, Subang Province, West Java Province, utilizes Ciasem River water, processed so that it has high water fall 17,61 m, water discharge design 1,100 l / s, hydraulic potential of 160 KW, turbine efficiency of 0.73, efficiency of generator 0.89, out put generator 120 KW, loses 4 KW and total electrical energy generated 116 KW. The purpose of development, to help people who were not reached PLN electricity, to empower the community.Empowerment begun from the time of development, where citizens are involved, which then able to become operators. The result of energy from PLTMH is sold to PLN, then the result is reduced for operational costing, maintenance cost, import cost / electricity payment used, depreciation cost of equipment taken from 10% of transactions, divided by two (50% for PT HidropirantiIntiBaktiSadaya, as shareholder) and 50% for Mekar Sari Cooperative, used for community empowerment. Since its operation, people who do not have electricity grid, are connected to electricity. In addition, the proceeds from the sale of electricity to PLN are used to help with the cost of education / scholarship, health, loans for business and cooperative operations. Empowerment implemented or managed Mekar Sari Cooperative. Along with the development of the era, empowerment assistance now being implemented includes: Health Sector in cooperation with Village Midwife, Savings and Loans and Scholarships for Primary School - 10 People and Junior High School - 5 People.